Abu Muhammad Abdullah ibn Muhammad Al-Sinhaji (about 500 / 561 ah) his activities and his contribution to scientific life in the Maghreb and the Mashreq - Tajnanat, mourad (The Algerian Historical Journal, 2026)
the purpose of this study is to reveal the personality of the theologian, scholar of hadith and linguist, Abdullah ibn Muhammad Ibn Al-Ashiri, he exercised the function of scribe among the in Andalusia; due to the exations , he was forced to emigrate to the Mashrek. He settled in Damascus,then Aleppo, and Baghdad. Ibn al-Ashiri was highly esteemed, students and scholars attended his classes. He had written many works which have unfortunately disappeared, only some of his titles are mentioned in historical sources. Ibn al-Ashiri died near Baalbeck in 561 ah, while traveling with Al-Malik al-Adil towards Homs, and buried in north of Baalbek.